2020
DOI: 10.35575/rvucn.n60a8
|View full text |Cite
|
Sign up to set email alerts
|

Salud mental y deserción en una población universitaria con bajo rendimiento académico

Abstract: La deserción es un fenómeno frecuente en las instituciones de educación superior (IES); puede estar asociado a diversos factores, entre ellos el estado de salud físico y mental. El presente estudio evaluó la prevalencia de problemas de salud mental en 69 estudiantes con bajo rendimiento académico, al inicio del semestre, por medio de entrevista estructurada aplicada por psiquiatra, y tres escalas autoaplicadas: ansiedad estado-rasgo, impulsividad de Barratt y el cuestionario de estilos de aprendizaje; fueron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
3
0
11
Order By: Relevance
“…However, the literature has shown that students with more siblings with a professional degree are less likely to drop out [47]. In addition, there is another set of individual determinant variables that can influence the completion of professional studies, such as health status [47,48], ethnicity [30,37,42], digital competencies and skills [49,50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the literature has shown that students with more siblings with a professional degree are less likely to drop out [47]. In addition, there is another set of individual determinant variables that can influence the completion of professional studies, such as health status [47,48], ethnicity [30,37,42], digital competencies and skills [49,50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on this interdisciplinary orientation of the study of dropout and the categorisation of the explanatory variables into the four determinants, this article is linked to the conceptual model described in Figure 1, which has been widely used in previous research (e.g., Barragán and González, 2017;Klein, 2019;Radovan, 2019;Kemper et al, 2020;Vera et al, 2020;Guzmán et al, 2021) as well as in the development of public policies such as in the Colombian case (Ministry of National Education, 2009), because it is adaptive to the educational modality or type of student population, the new realities of the higher education context, as well as allowing the development of explanatory and predictive models of dropout in higher education (Guzmán et al, 2021).…”
Section: Dropout and The Theoretical Reference Modelmentioning
confidence: 99%
“…Orellana et al (2021),Guzmán et al (2020a), Rodriguez Urrego (2019) andKara et al (2019), as well as recent empirical studies such asGuzmán et al (2021),Behr et al (2020),Kehm et al (2019),Barragán and González (2017), as well asVera et al (2020).…”
mentioning
confidence: 95%
“…Estos síntomas pueden llevar a una disminución de la motivación para estudiar, asistir a clases o participar en actividades académicas. (31) 3. Trastornos del Espectro Bipolar: Las fluctuaciones entre la manía y la depresión pueden causar inconsistencias en el rendimiento académico.…”
Section: Interacción Entre Bienestar Mental Y Rendimiento Académico E...unclassified